EVOLUTION OF CAROTENOID PIGMENTATION IN CACIQUES AND MEADOWLARKS (ICTERIDAE): REPEATED GAINS OF RED PLUMAGE COLORATION BY CAROTENOID C4‐OXYGENATION. (1st March 2014) - Friedman, Nicholas R.; McGraw, Kevin J.; Omland, Kevin E.
Abstract: Many animals use carotenoid pigments to produce yellow, orange, and red coloration. In birds, at least 10 carotenoid compounds have been documented in red feathers; most of these are produced through metabolic modification of dietary precursor compounds. However, it is poorly understood how lineages have evolved the biochemical mechanisms for producing red coloration. We used high‐performance liquid chromatography to identify the carotenoid compounds present in feathers from 15 species across two clades of blackbirds (the meadowlarks and allies, and the caciques and oropendolas; Icteridae), and mapped their presence or absence on a phylogeny. We found that the red plumage found in meadowlarks includes different carotenoid compounds than the red plumage found in caciques, indicating that these gains of red color are convergent. In contrast, we found that red coloration in two closely related lineages of caciques evolved twice by what appear to be similar biochemical mechanisms. The C4‐oxygenation of dietary carotenoids was responsible for each observed transition from yellow to red plumage coloration, and has been commonly reported by other researchers. This suggests that the C4‐oxygenation pathway may be a readily evolvable means to gain red coloration using carotenoids.